Gonadal development of Crassostrea gigas in Bahía San Quintín, Baja California, Mexico - CG Paniagua-Chávez; MJ Acosta-Ruiz (Ciencias Marinas, 1995)
The reproductive cycle of the Pacific oyster, Crassostrea gigas (Thunberg), presents significant differences (S [α = O.OS]) in September and October in the La Boca and Mina Vieja locations. The maximum gonadal index (GI) occurred in May and August at Mina Vieja with 32 and 34%, respectively and the minimum of 8% in October. In La Boca, the highest GI value of 37% was obtained in September and October while the lowest, 7%, was observed in April. Partial spawnings were observed from July through October in La Boca and from July to September in Mina Vieja, located in the internal area of Bahía San Quintín. An asynchrony was observed in both spawning and maturation between male and female oysters. The male:female ratio was 7:3 and hermaphroditism was less than 3%.